Mineral Content of Five Indigenous Leafy Vegetable from Bintulu Market, Sarawak Malaysia - S. R. Sarbini, Z. Muta Harah, S. Ainul Asyira, S. Noorasmah (Journal of Medicinal Herbs and Ethnomedicine, 2017)
Indigenous leafy vegetables commonly consumed by local people in Bintulu, Sarawak, Malaysia. Most people consumed this group of vegetable without knowing the nutrient contents and its importance to the health. Five indigenous leafy vegetables, Scorodocarpus borneensis, Pangium edule, Gnetum gnemon, Dracaena gracilis, and Helminthostachys zeylanica were selected and analysed to determine their mineral contents. The vegetables were bought from Bintulu native market and mineral elements were analysed using standard method of AOAC. The result showed that S. borneensis and D. gracilis contains high concentration of P, .P. edule contains high Ca, Cu and Mg, H. zeylanica had highest Zn, Fe, K and Na and G. gnemon showed high Mn. The PCA result performed three distinct groups with respect to the nutrient elements. Group A: G. gnemon and H. zeylanica which contains K, Na, Fe, Mn and Zn. Group B: S. borneensis and D. gracilis with high P content and Group C: P. edulewith high Ca, Cu and Mg. The study of mineral contents of the indigenous leafy vegetables can help to improve the efficiency of nutrient intake by local people and further information is required to enable the vegetables to be introduced as new crops.Â Â Keywords: mineral contents, nutrition, indigenous leafy vegetables, local people, health